1990
DOI: 10.1111/j.1432-1033.1990.tb15402.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a soluble form of human CD4

Abstract: CD4 is a glycoprotein that is expressed on the surface of a variety of cells of the immune system and is believed to participate in the interactions of these cells with antigen-presenting cells bearing the class I1 major histocompatability (MHC) antigens. CD4 also acts as the receptor for the human immunodeficiency virus (HIV) by binding to the viral glycoprotein gp120. Recombinant soluble CD4 (rCD4) is a truncated form of human CD4 that is secreted from transfected Chinese hamster ovary cells.This 368-amino-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 25 publications
(18 reference statements)
2
30
0
Order By: Relevance
“…In preliminary experiments (Figure 2; Harris et al, 1990), Asn-300 had been found to carry a mixture of endo H susceptible and endo H resistant oligosaccharides. To isolate oligosaccharides for structure elucidation, a sample (960 nmol) of the purified Asn-300-containing glycopeptides was first treated with endo H. At the conclusion of digestion, reversed-phase HPLC was used to recover the released oligosaccharides (which were detected by HPAE chromatography of aliquots of the reversed-phase HPLC column fractions) and the endo H resistant portion of the glycopeptide (not shown).…”
Section: "mentioning
confidence: 98%
See 2 more Smart Citations
“…In preliminary experiments (Figure 2; Harris et al, 1990), Asn-300 had been found to carry a mixture of endo H susceptible and endo H resistant oligosaccharides. To isolate oligosaccharides for structure elucidation, a sample (960 nmol) of the purified Asn-300-containing glycopeptides was first treated with endo H. At the conclusion of digestion, reversed-phase HPLC was used to recover the released oligosaccharides (which were detected by HPAE chromatography of aliquots of the reversed-phase HPLC column fractions) and the endo H resistant portion of the glycopeptide (not shown).…”
Section: "mentioning
confidence: 98%
“…This work included assignment of the three intrachain disulfide bonds and demonstration that both potential N-glycosylation sites are glycosylated. Tryptic mapping of enzymatically deglycosylated rCD4 revealed that Asn-300 carried a mixture of endo H resistant and endo H susceptible structures whereas all of the structures attached to Asn-271 were endo H resistant (Harris et al, 1990). The goal of the present study has been the detailed elucidation of the carbohydrate structures of CHO-expressed rCD4, including the distribution of structures at each of the two glycosylation sites.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…1C). Control experiments in which sCD4 was isolated with mAb Leu3a and probed with HRP-NeutrAvidin revealed no biotinylation, confirming that sCD4 does not contain unpaired cysteines (43) and indicating that disulfide bonds of sCD4 had not been reduced by PDI.…”
Section: The Surface Of Hiv-1 Target Cells Has a Reductive Functionmentioning
confidence: 99%
“…Various recombinant human glycoproteins synthe sized in CHO cells, such as y-interferon [9], FSH [10], E P O [ll, 12], plasminogen activator [13,14], HIV gp 120 [15], CD4 [16,17] and interleukin-5 [18] have been reported to have N-linked oligosaccharides with mono-, di-, tri-and tetra-antennary chains. They have a2-3 sialyl lactosamine structures at their carbohydrate chain terminals.…”
Section: Discussionmentioning
confidence: 99%